2018
DOI: 10.1136/bmjopen-2018-023803
|View full text |Cite
|
Sign up to set email alerts
|

Disability and morbidity among older patients in the emergency department: a Danish population-based cohort study

Abstract: ObjectivesThe objective was to describe the prevalence of geriatric conditions among older medical patients in the emergency department (ED) and the association with admission, mortality, reattendance and loss of independency.DesignPopulation-based prospective cohort study.SettingED of a large university hospital.ParticipantsAll medical patients ≥65 years of age from a single municipality with a first attendance to the ED during a 1-year period (November 2013 to November 2014).Primary and secondary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 67 publications
4
23
0
Order By: Relevance
“…The increased mortality rates observed in the aged patients visiting the ED in our study were of similar magnitudes as shown before [6, 16]. In the here presented data, patients in the oldest age group and with the lowest triage priority had a 16 and 21-fold increased risk for 7 and 30-days mortality compared to patients in the youngest age group.…”
Section: Discussionsupporting
confidence: 90%
“…The increased mortality rates observed in the aged patients visiting the ED in our study were of similar magnitudes as shown before [6, 16]. In the here presented data, patients in the oldest age group and with the lowest triage priority had a 16 and 21-fold increased risk for 7 and 30-days mortality compared to patients in the youngest age group.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the incremental risk of death across DSC classes was comparable in the two studies. Moreover, short and long-term mortality rate figures in the AIDEA cohort compare well to those reported by Tanderup et al : in a Danish study on 3775 subjects aged 65+ years accessing the ED, 30-day and 1-year cumulative mortality increased progressively, from 2.2% to 10.6% and from 8% to 39%, respectively, with the number of geriatric conditions (from 0 to 4), identified on the basis of comprehensive geriatric assessment 27. The similarity between Tanderup’s and our estimates provides further, indirect support to the external validity of the DSC: the absolute mortality risk is indeed crucial, more than HR, to take appropriate decisions on treatment level.…”
Section: Discussionsupporting
confidence: 85%
“…Their clinical presentation is frequently characterised not by a single, well-defined disease, but rather by an entangled combination of age-related changes, comorbidity, functional and cognitive impairment, polypharmacy and social problems. As a consequence, the risk of wrong triage, incorrect diagnosis and treatment, prolonged ED stay and inappropriate destination is substantial 27. Worsening disability, institutionalisation or death shortly after the ED access may be ultimate consequences 28…”
Section: Discussionmentioning
confidence: 99%
“…12 In the emergency department (ED), older adults commonly visit with severe illnesses, which have a high mortality rate and are at risk for the functional impairment after discharge. [13][14][15] Furthermore, an avoidable hospitalization due to dehydration costed approximately 1.14 billion USD in a year with higher charges when admitted from ED. 16 Detecting HD in these patients is crucial.…”
Section: Introductionmentioning
confidence: 99%